Agglomeration of carbonaceous particles in a pendant water slurry droplet; Colloids and Surfaces A: Physicochemical and Engineering Aspects; Vol. 703, pt. 2 - Islamova A. G. Anastasiya Gomilievna (2024, 2024)
Title screen.